PENGARUH SELF EFFICACY TERHADAP KINERJA DOSEN DENGAN MOTIVASI KERJA SEBAGAI VARIABEL INTERVENING PADA SEKOLAH TINGGI ILMU EKONOMI SAKTI ALAM KERINCI - Poni Yanita (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
The purpose of this study was to find out: 1) To what extent does self-efficacy influence the performance of STIE Sakti Alam Kerinci lecturers 2) To what extent does self-efficacy influence the work motivation of STIE Sakti Alam Kerinci lecturers 3) How far does work motivation influence the performance of STIE Sakti Alam Kerinci lecturers. The population in this study is the permanent lecturers of STIE Sakti Alam Kerinci, which currently number 43 people. The sampling technique is Total Sampling, namely the entire population is used as a sample, namely 43 permanent lecturers at STIE Sakti Alam Kerinci. Then a hypothesis test was carried out with the t test and the significance of a = 0.05. The results of the study show that (1) there is a significant influence between Self Efficacy on the work motivation of lecturers at STIE Sakti Alam Kerinci. (2) There is a direct effect between Self Efficacy on the Performance of STIE Sakti Alam Kerinci Lecturers. Self-Efficacy can indirectly influence the Performance of Lecturers at STIE Sakti Alam Kerinci through Work Motivation. Work Motivation can act as an intervening variable in Self Efficacy on Lecturer Performance. (3) There is a significant influence between work motivation on Lecturer Performance at STIE Sakti Alam Kerinci.